Turning Research of a Sowing Unit Based on Reversible Tractor - Findura, Pavol; Kollárová, Katarína; Nadykto, Volodymyr; Kyurchev, Volodymyr; Zhokin, Ivan; Надикто, Володимир Трохимович; Кюрчев, Володимир Миколайович; Жокін, Іван Олександрович (Nitra : Paradigm Publishing Services, 2024)
EN: Modern sowing machine-tractor units (MTU) can be divided into single-machine (single-module), two-machine (double-module), and three-machine (triple-module). The firsts, consisting of a tractor and a trailed/mounted seeder, are the most studied and, therefore, the most widespread. Two-module MTUs mainly use trailed or semi-mounted hitch and trailed seeders. The units of this type have been studied less. Three-module sowing complexes are even less common. Most are based on a trailed hitch and trailed seeders placed behind the tractor. There are samples of MTU with side-mounted seeding machines, but their knowledge is extremely insufficient. This paper examines a three-module MTU based on a tractor with reverse motion and a front semi-mounted hitch. One of the problems in using this sowing unit is the choice of design parameters that would ensure safe turning when manoeuvring on the headland. Theoretical and experimental studies have established that by increasing the side seeder's towbar length, MTU's safe turning under analysis with machines of a larger operating width can be performed with a smaller distance between their inner wheels and tractor's wheels (parameter d). If the coincidence condition of side seeders' wheel axes with the tractor wheels axe is met, an increase in the tractor track from 1.7 to 2.5 m allows for a decrease in the value of the distance d. This solution is especially effective when using seeders with an operating width of 3.6 m. In this case, the indicated decrease reaches a fivefold size, from 0.5 to 0.10 m. With the seeders' operating width of 5.4 m, the distance d can only be reduced by 1.4 times. But with this option for sowing MTU, it is possible to use a tractor with dual rear tyres and a parameter d value of 0.98 m. Actual oscillations in the distance d value within 0.28 ±0.01 m in the process of turning the studied sowing machine-tractor unit at a velocity of 2.2 m·s-1 are characterized by low variance (0.64·10-4 m2) and low (no more than 1.75 Hz) frequency. This allows us to consider this MTU's mode movement on the headland quite safe.
Keywords: turn; headland; turning radius; manoeuvring; kinematic length of the unit; поворот; поворотна смуга; радіус повороту; маневрування; кінематична довжина агрегату